Urinary dysfunction in patients with unsatisfactory results of surgical treatment of benign prostatic hyperplasia - S. Kh. Al-Shukri; T. G. Giorgobiani; R. E. Amdiy; A. S. Al-Shukri (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The study aimed to develop diagnostics and treatment of urinary dysfunction in patients with unsatisfactory results of surgery of benign prostatic hyperplasia (BPH). MATERIAL AND METHODS. The urodynamic studies were made for 93 (72,7 %) patients after transurethral resection of the prostate and 35 (27,3 %) patients after open adenomectomy. All the patients had urinary dysfunctions after surgery of BPH. RESULTS. Detrusor hyperactivity was revealed in 51 (39,9 %) patients. Detrusor hypoactivity was noted in 21 (16,4 %) patients. Combination of detrusor hyperactivity during storage phase and detrusor hypoactivity during emptying phase had 25 (19,5 %) patients. Infravesical obstruction was detected in 22 (17,2 %). Urgent incontinence was diagnosed in 10 cases. There were 9 patients with signs of stress and condition combined with predomination of stress component. Treatment depended on the causes of urination dysfunction. CONCLUSIONS. Results of urodynamic studies allowed doctors to implement pathogenically verified therapy of urinary dysfunction after surgery of benign prostatic hyperplasia and improve its efficacy.